2017
DOI: 10.1088/1757-899x/225/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variable Compression Ratio on Performance of a Diesel Engine Fueled with Karanja Biodiesel and its Blends

Abstract: Rapid exploration and lavish consumption of underground petroleum resources have led to the scarcity of underground fossil fuels moreover the toxic emissions from such fuels are pernicious which have increased the health hazards around the world. So the aim was to find an alternative fuel which would meet the requirements of petroleum or fossil fuels. Biodiesel is a clean, renewable and bio-degradable fuel having several advantages, one of the most important of which is being its eco-friendly and better knocki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…25 Mishra tested the Karanja oil diesel blend in a variable compression diesel engine and found an increase in engine performance at a compression ratio of 17.5 and a blend of 25% at all loading circumstances. 26 Attri et al found that CR of 17 exhibited improvement in thermal efficiency and control in BSFC by using 1-butanol blended diesel in a four-stroke CI engine. While an increment in the compression ratio up to 18 resulted in reduction of HC, CO, and NOx emissions.…”
Section: Introductionmentioning
confidence: 99%
“…25 Mishra tested the Karanja oil diesel blend in a variable compression diesel engine and found an increase in engine performance at a compression ratio of 17.5 and a blend of 25% at all loading circumstances. 26 Attri et al found that CR of 17 exhibited improvement in thermal efficiency and control in BSFC by using 1-butanol blended diesel in a four-stroke CI engine. While an increment in the compression ratio up to 18 resulted in reduction of HC, CO, and NOx emissions.…”
Section: Introductionmentioning
confidence: 99%
“…However, most benefits are related to minimal fuel consumption, minimal nitric oxides and particulate matter emissions [11]. To obtain superior performances, a cumulative method is required for improving the design process and final geometry, combustion process parameters [12][13][14][15] type of fuel [16] and other environmental parameters.…”
Section: Introductionmentioning
confidence: 99%